Transformation of Pesantren Education in the Digital Era: AI Innovation and Adaptation for Technology-Based Learning - Lestari, Tutik; Rahmayana, Audia; Agustiana, Fina (Electronic Integrated Computer Algorithm Journal, 2025)
Pesantren as a traditional Islamic educational institution faces challenges in navigating the digital era. Artificial Intelligence (AI) offers significant opportunities to enhance learning effectiveness, administrative systems, and educational management in pesantren. This article examines how AI can be adapted in pesantren education, covering implementation, benefits, and challenges. Using a qualitative approach and literature review, this study finds that AI can support curriculum management, personalize learning, and improve access to broader educational resources. However, AI adaptation also faces obstacles such as infrastructure limitations, human resources, and ethical considerations in applying technology within the pesantren environment. Therefore, an appropriate AI implementation strategy must be designed to align with pesantren values without eliminating its traditional characteristics.